Molecular Insight and Mode of Inhibition of α‐Glucosidase and α‐Amylase by Pahangensin A from Alpinia pahangensisRidl. Issue 6 (9th May 2019) - Loo, Kong Yong; Leong, Kok Hoong; Sivasothy, Yasodha; Ibrahim, Halijah; Awang, Khalijah
Abstract: The inhibition of carbohydrate‐hydrolyzing enzymes in human digestive organs is crucial in controlling blood sugar levels, which is important in treating type 2 diabetes. In the current study, pahangensin A (1 ), a bis‐labdanic diterpene characterized previously in the rhizomes of Alpinia pahangensis Ridl ., was identified as an active dual inhibitor for α ‐amylase (IC50 =114.80 μm ) and α ‐glucosidase (IC50 =153.87 μm ). This is the first report on the dual α ‐amylase and α ‐glucosidase inhibitory activities of a bis‐labdanic diterpene. The Lineweaver‐Burk plots of compound1 indicate that it is a mixed‐type inhibitor with regard to both enzymes. Based on molecular docking studies, compound1 docked in a non‐active site of both enzymes. The dual inhibitory activity of compound1 makes it a suitable natural alternative in the treatment of type 2 diabetes. Abstract :